(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The influence of anionic and nonionic micelles on phenyldiethanolamine reaction with potassium persulfate in aqueous solutions at 298 K has been studied. It has been established that in presence of both type micelles the reaction rate, determined by iodometric and colorimetric methods decreases. With enhance of surfactants initial concentration the magnitude of the slowing – down of the reaction rate increases. On the basis of kinetic data the constants of amine binding with E-30 micelles have been calculated. It has been assumed that the first product of amine oxidation is localized in micelle hydrophobe nuclei.